Operations research proceedings 2003: selected papers of the International Conference on Operations Research (OR 2003), Heidelberg, September 3 - 5, 2003 ; with 51 tables - Ahr, Dino; Fahrion, Roland; Oswald, Marcus; Reinelt, Gerhard (Springer, 2004)
This proceedings volume contains a selection of papers presented at the International Conference on Operations Research (OR 2003). The contributions cover the broad interdisciplinary spectrum of Operations Research and present recent advances in theory, development of methods, and applications in practice. Subjects covered are Revenue Management, Telecommunication, Information Technology, Production, Logistics, Supply Chain Management, Services, Transportation, Traffic, Scheduling, Project Management, Marketing, Data Analysis, Energy, Environment, Health, Finance, Banking, Insurances, Simulation, Continuous Optimization, Discrete and Combinatorial Optimization, Applied Probability, Artificial Intelligence, Fuzzy Logic, Neural Networks, Econometrics, Statistics, Mathematical Economics, Decision Theory, Experimental Economics, Game Theory, Auctioning, Web Technology, Knowledge Management, Decision Support Systems. TOC:GOR Awards.- Revenue Management.- Telecommunication and Information Technology.- Production, Logistics and Supply Chain Management.- Services, Transportation and Traffic.- Scheduling and Project Management.- Marketing and Data Analysis.- Energy, Environment and Health.- Finance, Banking and Insurances.- Simulation.- Continuous Optimization.- Discrete and Combinatorial Optimization.- Applied Probability.- Artificial Intelligence, Fuzzy Logic and Neural Networks.- Econometrics, Statistics, Mathematical Economics and Decision Theory.- Experimental Economics, Game Theory and Auctioning.- Web Technology, Knowledge Management and Decision Support Systems
Literaturangaben
Beitr. teilw. dt., teilw. engl
Keywords: Konferenzschrift -- 2003 -- Heidelberg; Operations Research